2001
DOI: 10.1121/1.4777645
|View full text |Cite
|
Sign up to set email alerts
|

Rear pharyngeal wall placement during vowel production

Abstract: While the rear pharyngeal wall has been assumed to be stationary during speech, this needs to be confirmed. The present study used midsagittal magnetic resonance images to determine whether the posterior pharyngeal wall shows vowel-specific movement during the sustained production of 11 English vowels. Distances were measured between the most posterior portion of the vertebral body and the pharyngeal wall at four points. The first traversed the junction between the dens and body of the second vertebra (C2). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…One study (Stone 1990) found that for vowels, /s/ and /l/, only about 1 cm of the tip is lost (comparable to X-ray Microbeam and EMMA tracking systems, which typically position the first pellet 1 cm from the tip). Another study (Magen & Kang 2001) shows the stability of the rear pharyngeal wall during the full range of English vowels, suggesting that tongue root measurements alone are sufficient to approximate pharyngeal constrictions for English vowels. To further mitigate these limitations, additional transducer pressure can improve tongue tip imaging, and where more precise measurements are required, tracking devices can be used to correct for position.…”
Section: Description Of Methodsmentioning
confidence: 99%
“…One study (Stone 1990) found that for vowels, /s/ and /l/, only about 1 cm of the tip is lost (comparable to X-ray Microbeam and EMMA tracking systems, which typically position the first pellet 1 cm from the tip). Another study (Magen & Kang 2001) shows the stability of the rear pharyngeal wall during the full range of English vowels, suggesting that tongue root measurements alone are sufficient to approximate pharyngeal constrictions for English vowels. To further mitigate these limitations, additional transducer pressure can improve tongue tip imaging, and where more precise measurements are required, tracking devices can be used to correct for position.…”
Section: Description Of Methodsmentioning
confidence: 99%